THE INFLUENCE OF FLASH SALES AND AI-POWERED PRODUCT REVIEWS ON PURCHASE INTENTION OF AMAZON PRODUCTS IN INDONESIA - Adetia, Mayang salva; Yacob, Syahmardi; Musnaini, Musnaini (Journal of Business Studies and Management Review, 2025)
This study aims to examine the influence of flash sales and AI-powered product reviews on purchase intention toward Amazon products in Indonesia. A quantitative approach was used, with data collected through a questionnaire distributed to 100 respondents. The data were analyzed using SmartPLS 4 to assess validity, reliability, and both direct and indirect relationships among variables. The results show that flash sales do not have a significant direct effect on purchase intention. In contrast, AI-powered product reviews have a positive and significant influence on purchase intention. Furthermore, flash sales have a significant indirect effect on purchase intention when mediated by AI-powered product reviews. These findings suggest that the integration of AI technology in product reviews can enhance the effectiveness of promotional strategies like flash sales in driving consumer purchase intention.